Pengaruh Media Promosi (Periklanan, Wiraniaga dan Promosi Penjualan) terhadap Loyalitas Nasabah pada PT. BPR Trisurya Bumindo Bandar Lampung - Yudiana Sari (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2022)
BPR Trisurya Bumindo Bandar Lampung has a potential market, namely all customers in Lampung, especially Bandar Lampung, but there are several problems that will be investigated, namely knowing the effect of promotional media (advertising, salespeople and sales promotions) on customer loyalty at PT. BPR Trisurya Bumindo Bandar Lampung. The research method used in this research is library research and field research through interviews and distributing questionnaires to customers of BPR Trisurya Bumindo Bandar Lampung. The results showed that the results of calculations using multiple linear regression analysis showed that overall advertising and sales promotion media had a significant influence on customer loyalty at BPR Trisurya Bumindo Bandar Lampung. Keywords: promotion, advertising, salesperson, sales